IMPLEMENTASI AKAD MUSYARAKAH MUTANAQISHAH DI LEMBAGA KEUANGAN ISLAM - Syahruddin Kadir; Mukhtar Lutfi; Nasrullah Bin Sapa; Abd. Hafid (Islamic Economic and Business Journal, 2022)
Some consumptive financing at Bank Muamalat and BMT are intended for customers such as mortgage products (home ownership) and vehicles, several types of contracts are executed, namely Musyarakah Mutanaqishah (MMQ). However, financing in the Musyarakah Mutanaqishah (MMQ) contract pattern still faces common problems. This study focuses on knowing the implementation of the Musyarakah Mutanaqishah (MMQ) contract on housing and vehicle financing. The research method used is a descriptive qualitative method with a literature review approach with data collection techniques namely literature study. The results showed that the implementation of the MMQ contract on housing and vehicle financing at Bank Muamalat and BMT was in line with DSN MUI Fatwa No. 73/DSN-MUI/XI/2008 concerning Musyarakah Mutanaqishah (MMQ), due to the existence of terms and conditions that there is a capital contribution of both parties between Islamic financial institutions and customers. The customer asks the financial institution to issue a partnership capital for the purchase of a house/vehicle, then the financial institution also includes partial/complementary capital so that it is referred to as an association/musyarakah then the customer pays the rent, and shares the proceeds with the bank.